Testosterone undecanoate and testosterone enanthate injections are both effective and safe in transmen over 5 years of administration. (12th August 2018) - Gava, Giulia; Mancini, Ilaria; Cerpolini, Silvia; Baldassarre, Maurizio; Seracchioli, Renato; Meriggiola, Maria C.
Summary: Objective: To retrospectively evaluate and compare safety and efficacy of short and long‐acting testosterone (T) parenteral formulations over 5 years in transmen. Design and methods: Fifty transmen between 21 and 42 years of age were enrolled. Twenty‐five received T undecanoate 1000 mg IM (weeks 0 and 6 then every 12‐16 weeks), and 25 received T enanthate 250 mg IM (every 3‐4 weeks). Hormonal and biochemical parameters, anthropometric characteristics and blood pressure were assessed at baseline and then every 12 months. Body composition was evaluated at baseline and then after 1, 3 and 5 years of T treatment. Global satisfaction was assessed at baseline and after 1 and 5 years. Results: Both T formulations led to amenorrhoea in all subjects within 1 year of T administration. Both T treatments led to a similar increase in haemoglobin and haematocrit which always remained within the physiological range. T administration was associated with an increase in total cholesterol, low‐density lipoprotein cholesterol and triglycerides and a slight reduction in high‐density lipoprotein cholesterol. Coagulative and glucidic profiles and blood pressure did not change significantly in either group. Body weight and BMI showed a slight but not significant increase in both groups, while lean mass rose significantly in both groups. Global satisfaction was increased at years 1 and 5 in both groups. Conclusions: Preliminary results from this pilot study suggest that administration of either TU or TE for 5 years in young transmen is both effective and safe. Our study presents the longest follow‐up published so far reporting no adverse events and these data are consistent with previous reports with a shorter follow‐up.